REMOVAL OF PARAFFIN WAX DEPOSITION BY MAGNETIC FIELD - Hasbullah, Nurathirah (Universiti Teknologi PETRONAS, 2011)
The problem of paraffin wax deposition in the wells as well as the surface facilities has presented a chalhmge to petroleum industry since the first wells were drilled. Magnetic field is one of th11 solutions to remove paraffin wax deposition inside the flowlines by altering the chemical, mechanical, electrical and thermal properties of the crude oil as it passes through tljr mono-pole magnetic field. Chai Set Lee, Use of Magnetic Field in . i Paraffin Wax Deposition Control for Surface Facilities (2008) and Nurhakimah Bt Mohd Aman, Investigation on The Removal of Paraffin Wax Deposition By Magnetic Field (2009) reported an experimental study on the influence of magnetic field on wax deposition removal and viscosity reduction. Chat Set Lee and Nurhakimah Bt Mohd Aman, both reported the configuration where the pipe is placed along the length of each magnet, on the top of the pipe are both South poles while at the bottom are the north poles displayed tjw best magnetic lines where all the line were at the right angle to the direction. This rpnfiguration is used in the experiment with different number of magnets, crude oil flow rate and the operational temperature to ensure the efficiency of the magnetic field to removed paraffin wax deposition. Lack of precise scientific explanation of magnetic field on paraffin crystallization process makes the experts in scale and paraffin control like Schlumberger and Nalco Chern believe that the magnetic field is still new and it is not yet proven in the real application. Therefore, the objective of this study is tp find the precise scientific explanation on the effectiveness of the magnetic field to remove the wax deposition. The effect of the crude oil temperature, crude oil flow rat~< and the number of magnets used are taking into consideration in order to obtain precise result. Based on the experiment, the effectiveness of the magnetic field has been proven which reduce the wax deposition by 2.067% and found to be the most economical technique for wax deposition removal. However, for the industry application, the magnetic strength, the operation temperature and the flow rate of the crude oil needed some modification to ensure the ability of the magnetic field to remove wax deposition. Hopefully, the result from this project can be significant impact to industry to solve the paraffin wax deposition problems in the production phase